2023
DOI: 10.3390/ijms24076156
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Reactivation as a New Predictor of Achieving Remission or Lupus Low Disease Activity State in Patients with Systemic Lupus Erythematosus with Cutaneous Involvement

Abstract: Although Epstein–Barr virus (EBV) reactivation has long been associated with the pathogenesis of systemic lupus erythematosus (SLE), many aspects of this relationship remain unclear. Our objective was to investigate the association between EBV reactivation and the achievement of SLE remission and lupus low disease activity state (LLDAS) over a six-month period. Clinical, laboratory, and virological tests (anti-EBV antibodies and EBV DNA) were performed among 51 patients with the active form of SLE on two occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Interestingly, EBV VCA IgM results of the 42‐year‐old patient was positive representing an acute EBV infection. To date, there has been multiple studies approving the association of SLE flare and EBV infection similar to our patient 8,9 . In a cross‐sectional study of 40 patients with SLE, the EBV test reported positive in 67.5%, while half of patients had active disease 10 .…”
Section: Case Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, EBV VCA IgM results of the 42‐year‐old patient was positive representing an acute EBV infection. To date, there has been multiple studies approving the association of SLE flare and EBV infection similar to our patient 8,9 . In a cross‐sectional study of 40 patients with SLE, the EBV test reported positive in 67.5%, while half of patients had active disease 10 .…”
Section: Case Discussionsupporting
confidence: 64%
“…To date, there has been multiple studies approving the association of SLE flare and EBV infection similar to our patient. 8,9 In a cross-sectional study of 40 patients with SLE, the EBV test reported positive in 67.5%, while half of patients had active disease. 10 The viral load was significantly higher in patients with active disease independent of immunosuppressive medication.…”
Section: Case Discussionmentioning
confidence: 99%